Impact of Irradiation on the Pharmacokinetics and Biotransformation of Tamoxifen - Cheng, Yung-Yi; Zheng, Teresa; Chang, Michael W.; Dalley, Jeffrey W.; Chen, Yu-Jen; Tsai, Tung-Hu; Hsieh, Chen-Hsi (Frontiers in Oncology, 2022)
Background: The optimal procedure for combining radiotherapy (RT) with tamoxifen treatment is controversial as radiotherapy may alter the pharmacokinetics and biotransformation of tamoxifen. The present study investigated this potential interaction by assessing the pharmacokinetics of tamoxifen during concurrent and sequential radiotherapy. Method: Plasma tamoxifen concentration was measured in rats with or without RT 2.0 Gy (RT2.0Gy) or 0.5 Gy (RT0.5Gy) with ultra-high performance liquid chromatography-tandem mass spectrometry after tamoxifen administration (10 mg/kg, p.o., n=6). Tamoxifen was either administered one hour after RT (concurrent condition) or twenty-four hours after RT (sequential condition). Results: Pharmacokinetic data analysis demonstrated that the area under curve (AUC) and half-life of tamoxifen was 2004 ± 241 hr ng/mL and 6.23 ± 1.21 hr, respectively after tamoxifen administration (10 mg/kg, p.o.). The respective conversion rate of 4-hydroxytamoxifen, N-desmethytamoxifen, and endoxifen for tamoxifen metabolism was 20, 16, and 5 %. The AUC value of tamoxifen in the RT0.5Gy group was 1.5 to 1.7-fold higher than in the sham and RT2.0Gy groups. The relative bioavailability of tamoxifen at concurrent RT0.5Gy and RT2.0Gy groups ranged from 127 - 202% and 71 - 152%, respectively. The magnitude of endoxifen, which converted from 4-hydroxytamoxifen and N-desmethyltamoxifen increased 3 to 5-fold in the concurrent RT groups. By contrast, the AUC of tamoxifen decreased by roughly 24% in the sequential RT2.0Gy group. The conversion ratio of endoxifen was four times higher than in the sequential RT2.0Gy group compared with rats not exposed to RT. Conclusion: The current study provides advanced pharmacokinetic data to confirm the interaction between RT and hormone therapy. Our findings indicate that RT facilitates the metabolism of tamoxifen to active metabolites and thus implie that combination RT-tamoxifen has potential benefits for the treatment of hormone-dependent breast cancer.